How do Australian women cope with pelvic girdle pain during pregnancy? A qualitative study protocol. Issue 7 (16th July 2018) - Ceprnja, Dragana; Chipchase, Lucinda; Liamputtong, Pranee; Gupta, Amitabh
Abstract : Introduction: Pelvic girdle pain is commonly experienced during pregnancy and results in significant physical, psychosocial and work-related challenges. Few studies have investigated the lived experiences of pregnant women with pelvic girdle pain and their coping strategies. There is a need to develop a greater understanding of this prevalent condition among Australian women. Thus, this study seeks to gain information about the impact of pelvic girdle pain on daily life and how women cope with this condition during pregnancy. Methods and analysis: A qualitative research design, situated within a phenomenological framework, is adopted. The participants will be invited to describe their lived experiences of pregnancy-related pelvic girdle pain, the impact on their daily life and the strategies they use to cope with the condition. A stratified purposive sample will be undertaken to ensure the sample provides information-rich cases representative of women with pregnancy-related pelvic girdle pain. Face-to-face, individual, semistructured interviews will be conducted with participants at Westmead Hospital, Sydney, Australia. A solicited diary will be offered to any participants who may find attending the interview difficult. All participants will also be invited to attend a focus group session. The different methods of data collection used in this study will allow for triangulation, thereby increasing the trustworthiness of findings. Ethics and dissemination: Ethical approval has been granted by the Human Research Ethics Committees of Westmead Hospital, Sydney, and Western Sydney University, Sydney. Dissemination of results will be via journal articles and conference presentations.